A method for preparing a flexible thermoelectric film with strong texture and high thermoelectric performance

By employing spark plasma sintering with carbon coating and through holes on insulating substrates, the method addresses the limitations of flexible thermoelectric films, enhancing their density, orientation, and electrothermal conversion performance, resulting in efficient and flexible thermoelectric films suitable for heat dissipation applications.

CN115188877BActive Publication Date: 2025-01-03WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210891650.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-27
Publication Date
2025-01-03
Estimated Expiration
2042-07-27

AI Technical Summary

Technical Problem

The low electrothermal transport performance of flexible thermoelectric films, particularly those based on bismuth telluride, limits their application in heat dissipation of electronic components due to poor density, orientation, and electrothermal conversion efficiency, especially when using insulating substrates that are prone to breakdown and uneven temperature distribution during spark plasma sintering.

Method used

A method involving spark plasma sintering with carbon coating and through holes on insulating substrates, combined with a traditional printing process, to enhance the density, orientation, and electrothermal conversion performance of flexible thermoelectric films.

Benefits of technology

The method achieves high-density, highly oriented flexible thermoelectric films with improved electrothermal conversion performance, ensuring flexibility and uniformity, and can provide efficient cooling capabilities comparable to bulk materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115188877B_ABST
    Figure CN115188877B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a flexible thermoelectric film with strong texture and high thermoelectric performance, comprising the following steps: 1) preparing a thermoelectric slurry, transferring the slurry to a film substrate by a printing method, and preparing a thermoelectric film after drying; 2) arranging carbon paper on the surface and side of the obtained thermoelectric film; 3) performing discharge plasma sintering to obtain a flexible thermoelectric film with strong texture and high electrothermal conversion performance. The present invention can effectively suppress the problems of insulation material breakdown and uneven temperature distribution that are easily caused during the discharge plasma sintering process by arranging through holes on the substrate, thereby realizing the effective application of the discharge plasma sintering technology in the field of high-performance flexible thermoelectric film preparation; the obtained thermoelectric film has the advantages of strong texture, high densification and high electrothermal conversion performance while ensuring flexibility, and the preparation method involved is simple and easy to operate, low cost, and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional materials, and in particular relates to a method for preparing a flexible thermoelectric film with strong texture and high thermoelectric performance. Background Art

[0002] In-plane heat dissipation technology based on flexible thermoelectric film cooling is expected to provide a solution for efficient in-plane heat dissipation of electronic devices, but the low electrothermal transport performance of flexible thermoelectric films seriously restricts the application of this technology in the heat dissipation of electronic components. Bismuth telluride-based thermoelectric materials are currently the best performing and only commercially applied thermoelectric materials near room temperature. Bismuth telluride-based compounds belong to the trigonal crystal system and have a crystal structure composed of stacked hexagonal layered structures. A large number of theoretical and experimental studies have shown that (000l) preferentially oriented thermoelectric films have excellent electrothermal transport properties. However, the (000l) preferential orientation of all reported bismuth telluride-based thermoelectric films is generally low, especially the thermoelectric films prepared by low-cost printing methods have almost no orientation. This is a key problem that causes the poor thermoelectric performance of flexible bismuth telluride-based films and the lack of commercial applications.

[0003] Spark plasma sintering, also known as field-assisted sintering, is a rapid solid-phase sintering and densification technology developed in recent years. This sintering technology uses strong DC pulse current to cause discharge between adjacent sintering materials. The graphite mold and sintering materials are subjected to Joule heat to produce instantaneous high temperature. Under the action of sintering pressure, the self-heating sintering materials are subjected to axial pressure and finally complete the densification process. This sintering method has the characteristics of fast heating rate, short sintering time, and good densification effect. It has been widely used in the preparation of bulk thermoelectric materials. In recent years, continuous research has found that the use of spark plasma sintering technology can obtain bulk thermoelectric materials with dense structure, excellent mechanical properties and thermoelectric properties. However, since the spark plasma sintering process uses strong DC pulse current to produce discharge between adjacent sintering materials, this requires that all materials should have good electrical and thermal conductivity. However, most flexible films use insulating substrates as substrates, which limits the application of spark plasma sintering technology in the process of film sintering densification (insulating substrates are prone to uneven temperatures, and the film is prone to breakdown and damage; and the slow heating preparation is prone to low film performance and unevenness). At present, there are no reports on the use of spark plasma sintering technology in the preparation of thermoelectric films both internationally and domestically. Summary of the invention

[0004] The main purpose of the present invention is to propose a method for preparing a thermoelectric film in response to the problems of poor density, low orientation and deteriorated electrothermal conversion performance of existing organic / inorganic composite flexible thermoelectric films. The preparation method is simple and controllable and can effectively improve the density, orientation and electrothermal conversion performance of organic / inorganic composite flexible thermoelectric films.

[0005] To achieve the above purpose, the technical solution provided by the present invention is:

[0006] A method for preparing a flexible thermoelectric film with strong texture and high thermoelectric performance comprises the following steps:

[0007] 1) preparing a thermoelectric slurry, transferring the slurry onto an insulating film substrate by a printing method, and preparing a thermoelectric film after drying;

[0008] 2) placing carbon paper on the side of the obtained thermoelectric film;

[0009] 3) Spark plasma sintering is performed to obtain a flexible thermoelectric film with strong texture and high electrothermal conversion performance.

[0010] Preferably, a through hole perpendicular to the surface of the substrate is provided on the thin film substrate; this can effectively improve the problems of insulation material breakdown and uneven temperature distribution that are easily caused during the spark plasma sintering process.

[0011] In the above solution, the method for setting the through hole is selected from at least one of laser etching, chemical etching or drilling.

[0012] In the above scheme, the through hole is arranged in a direction perpendicular to the surface of the film substrate; the cross-sectional area of ​​the through hole is 0.05 to 0.3 mm 2 , the through hole spacing is more than 1mm.

[0013] Furthermore, for the insulating film substrate used in the laboratory, the through-hole spacing is set to 1 to 5 mm.

[0014] Preferably, the through holes are evenly arranged on the surface of the film substrate.

[0015] More preferably, the through holes are evenly arranged in an array distribution manner on the surface of the film substrate.

[0016] Furthermore, the through hole has a shape of a triangle, a square, a circle, or a polygon.

[0017] In the above solution, the insulating film substrate is made of any one of polyimide, polyethylene terephthalate, polyethylene naphthalate, glass cloth and the like.

[0018] In the above scheme, the preparation method of the thermoelectric slurry in step 2) is to add the thermoelectric powder into the binder solution, and mechanically stir and ultrasonically disperse the mixture to make it uniformly mixed.

[0019] In the above scheme, the thermoelectric powder in the thermoelectric slurry in step 2) is p-type or n-type Bi2Te 3-x Se x (x=0-3) or Bi2-x Sb x Te3 (x=0-2) based thermoelectric material; the content of thermoelectric powder in the thermoelectric slurry is 40-80wt%.

[0020] In the above scheme, the binder in the binder solution in step 2) is at least one of epoxy resin, polyvinylidene fluoride resin, acrylic resin, polyurethane resin, cellulose resin, etc.

[0021] In the above scheme, the solvent in the binder solution in step 2) is at least one of water, ethanol, butyl glycidyl ether, dimethyl ester, n-propyl ester, acetone, butanone, etc.

[0022] In the above solution, the adhesive solution also contains a curing agent, a catalyst, a diluent or other additives.

[0023] Furthermore, the curing agent may be selected from methyl hexahydrophthalic anhydride, methyl tetrahydrophthalic anhydride, dodecyl succinic anhydride, m-phenylenediamine, etc.; the catalyst may be selected from 2-ethyl-4-methylimidazole, quaternary ammonium salt, etc.; the diluent may be selected from butyl glycidyl ether, ethylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, etc.

[0024] In the above scheme, in the binder solution, the content of the binder is more than 20wt%; the content of the curing agent is less than 15wt%; the content of the catalyst is less than 5wt%; and the content of the diluent is less than 60wt%.

[0025] In the above scheme, the printing method in step 2) is selected from any one of screen printing, spin coating, brushing, dispensing printing, inkjet printing, gravure printing, etc.

[0026] In the above scheme, the spark plasma sintering system in step 3) includes: initial pressure of 2-15MPa, sintering temperature of 200-400°C, sintering pressure of 15-50MPa, and heat preservation and pressure holding sintering time of 5-30min; wherein the heating rate adopted is 5-40°C / min.

[0027] Furthermore, the pressurization rate involved in the spark plasma sintering process is 0.15-4.5 MPa / min.

[0028] Preferably, for a thin film substrate without through holes, the heating rate used in the spark plasma sintering is 6-9° C. / min; for a thin film substrate with through holes, the heating rate used in the spark plasma sintering is 9-30° C. / min.

[0029] Preferably, for a thin film substrate with through holes, the optimal conditions for the spark plasma sintering are: initial pressure of 2-10 MPa, sintering temperature of 280-320° C., heating rate of 9-15° C. / min, and heat preservation time of 8-15 min.

[0030] The flexible bismuth telluride-based film prepared according to the above scheme has high (000l) orientation, high density and excellent electrothermal conversion performance and refrigeration performance.

[0031] In the above solution, the thickness of the flexible bismuth telluride-based film is 20 to 300 μm.

[0032] In the above scheme, the (000l) preferred orientation factor of the flexible bismuth telluride-based film is as high as 78%, and the power factor can reach 2.62mW·K -2 ·m -1 The cold end temperature difference can reach 1.3K; the density can reach 6.85g / cm 3 .

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] 1) The present invention successfully applies the spark plasma sintering technology to the preparation of flexible thermoelectric films for the first time by carbon coating the thermoelectric film samples and combining it with the improvement of the spark plasma sintering process. It also combines it with the traditional printing method to achieve low-cost and controllable preparation of flexible thermoelectric films.

[0035] 2) The present invention further makes through holes on the insulating substrate, which can effectively suppress the breakdown of the insulating material and the uneven temperature distribution that are easily caused during the spark plasma sintering process, further simplify the preparation process and improve the uniformity of the electrical transport performance;

[0036] 3) The obtained thermoelectric film not only ensures flexibility, but also obtains strong texture, high densification and high electrothermal conversion performance, which can provide a new idea for the preparation of high-performance flexible thermoelectric films. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Bi prepared in Example 1 0.5 Sb 1.5 The relationship between the conductivity (a), Seebeck coefficient (b), power factor (c) and test temperature of Te3 thermoelectric film at different positions (edge ​​and middle);

[0038] Figure 2 Bi prepared in Example 2 0.5 Sb 1.5The relationship between the conductivity (a), Seebeck coefficient (b), power factor (c) and test temperature of Te3 thermoelectric film at different positions (edge ​​and middle);

[0039] Figure 3 Bi prepared in Examples 1 to 5 0.5 Sb 1.5 X-ray diffraction pattern (XRD) of Te3 thermoelectric thin film;

[0040] Figure 4 a is Bi prepared in Example 2 0.5 Sb 1.5 Backscattered electron image (BEI) of a cross section of a Te3 thermoelectric thin film. Figure 4 b~f are respectively Bi prepared in Examples 1~5 0.5 Sb 1.5 Secondary electron image (SEI) of a cross section of a Te3 thermoelectric thin film;

[0041] Figure 5 Bi prepared in Examples 1 to 5 0.5 Sb 1.5 (a) is a graph showing the relationship between the conductivity (a), Seebeck coefficient (b), power factor (c) and test temperature of the Te3 thermoelectric film; (d) is a graph showing the relationship between the hot and cold end temperatures of the single-arm device assembled using the films prepared in Example 1 and Example 5 and the test time. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] In the following examples, Bi 0.5 Sb 1.5 The preparation method of Te3 powder includes the following steps: after the p-type bismuth telluride BST crystal rod is crushed and sieved, BST thermoelectric powder with a particle size of less than 120μm is obtained, 10g of BST thermoelectric powder is accurately weighed and added to a 200mL ball mill, mixed evenly with 50mL of anhydrous ethanol, argon gas is introduced for protection, and ball milling is carried out at a speed of 200rpm / min for 2h to obtain flat BST thermoelectric powder.

[0044] Example 1

[0045] A method for preparing a flexible thermoelectric film with strong texture and high thermoelectric performance, using a film substrate without through holes, the specific steps are as follows:

[0046] 1) Accurately weigh 10g Bi 0.5 Sb1.5 Te3 powder, 0.612g of bisphenol F diglycidyl ether epoxy resin, 0.521g of methyl hexahydrophthalic anhydride, 0.123g of 2-ethyl-4-methylimidazole, and 1.8g of butyl glycidyl ether were uniformly dispersed by ultrasonication after mechanical stirring to obtain a thermoelectric slurry;

[0047] The polyimide substrate was ultrasonically cleaned in anhydrous ethanol for 15 min and then air-dried. The thermoelectric slurry was printed on the substrate using a screen printer and vacuum dried at 100 °C for 3 h to obtain Bi 0.5 Sb 1.5 Te3 thermoelectric thin film;

[0048] 2) placing a piece of carbon paper of the same size on the upper and lower sides of the thermoelectric film obtained in step 1), and then wrapping the carbon paper around the side of the thermoelectric film to obtain a thermoelectric film wrapped with carbon paper;

[0049] 3) The carbon paper-wrapped thermoelectric film obtained in step 2) is placed in a discharge plasma sintering furnace, and the initial sintering pressure is set to 7 MPa, the sintering temperature is set to 300°C, the sintering pressure is set to 15 MPa (the heating and pressure increase time is about 45 min), and the heating rate is set to 6°C / min; the temperature and pressure are maintained for 10 min to obtain a final Bi film with a thickness of about 150 μm. 0.5 Sb 1.5 Te3 thermoelectric thin film.

[0050] Example 2

[0051] A method for preparing a flexible bismuth telluride-based film with strong texture and high thermoelectric performance, using a film substrate with through holes, comprises the following steps:

[0052] 1) using laser etching technology to make circular through holes with a diameter of 300 μm and a spacing of 1500 μm on a polyimide substrate with a diameter of 25 mm and a thickness of 125 μm in an array distribution manner (perpendicular to the surface of the polyimide substrate, the same below), and then ultrasonically cleaning it in anhydrous ethanol for 15 minutes and then drying it to obtain a thin film substrate with through holes;

[0053] 2) Accurately weigh 10g Bi 0.5 Sb 1.5 Te3 powder, 0.612 g of bisphenol F diglycidyl ether epoxy resin, 0.521 g of methyl hexahydrophthalic anhydride, 0.123 g of 2-ethyl-4-methylimidazole, and 1.8 g of butyl glycidyl ether were mechanically stirred and then ultrasonically dispersed to obtain a thermoelectric slurry;

[0054] The obtained thermoelectric paste was printed on a thin film substrate with through holes using a screen printer and dried in vacuum at 100 °C for 3 h to obtain Bi 0.5 Sb 1.5 Te3 thermoelectric thin film;

[0055] 3) placing a piece of carbon paper of the same size on the upper and lower sides of the thermoelectric film obtained in step 2), and then wrapping the carbon paper around the side of the thermoelectric film to obtain a thermoelectric film wrapped with carbon paper;

[0056] 4) The obtained Bi 0.5 Sb 1.5 The Te3 thermoelectric film was placed in a spark plasma sintering furnace, and the initial sintering pressure was set to 7MPa, the sintering temperature was 300℃, the sintering pressure was 15MPa (the heating and pressure increase time was about 45min), and the heating rate was 6℃ / min; the temperature and pressure were kept for 10min to obtain a Bi film with a final thickness of about 150μm. 0.5 Sb 1.5 Te3 thermoelectric thin film.

[0057] Example 3

[0058] A method for preparing a flexible bismuth telluride-based film with strong texture and high thermoelectric performance comprises the following steps:

[0059] 1) using laser etching technology to form circular through holes with a diameter of 300 μm and a spacing of 1500 μm on a polyimide substrate with a diameter of 25 mm and a thickness of 125 μm in an array distribution manner, and then placing it in anhydrous ethanol for ultrasonic cleaning for 15 minutes and then drying it; a thin film substrate with through holes is obtained;

[0060] 2) Accurately weigh 10g Bi 0.5 Sb 1.5 Te3 powder, 0.612 g of bisphenol F diglycidyl ether epoxy resin, 0.521 g of methyl hexahydrophthalic anhydride, 0.123 g of 2-ethyl-4-methylimidazole, and 1.8 g of butyl glycidyl ether were mechanically stirred and then ultrasonically dispersed to obtain a thermoelectric slurry;

[0061] The obtained thermoelectric paste was printed on a thin film substrate with through holes by screen printing and dried in vacuum at 100°C for 3 h. 0.5 Sb 1.5 Te3 thermoelectric thin film;

[0062] 3) placing a piece of carbon paper of the same size on the upper and lower sides of the thermoelectric film obtained in step 2), and then wrapping the carbon paper around the side of the thermoelectric film to obtain a thermoelectric film wrapped with carbon paper;

[0063] 4) The obtained Bi 0.5 Sb 1.5The Te3 thermoelectric film was placed in a spark plasma sintering furnace, and the initial sintering pressure was set to 7MPa, the sintering temperature was 250℃, the sintering pressure was 15MPa, the heating rate was 6℃ / min, and the temperature was kept at 10min to obtain a Bi film with a final thickness of about 150μm. 0.5 Sb 1.5 Te3 thermoelectric thin film.

[0064] Example 4

[0065] A method for preparing a flexible bismuth telluride-based film with strong texture and high thermoelectric performance, using a film substrate with through holes, comprises the following steps:

[0066] 1) using laser etching technology to form circular through holes with a diameter of 300 μm and a spacing of 1500 μm on a polyimide substrate with a diameter of 25 mm and a thickness of 125 μm in an array distribution manner, and then placing it in anhydrous ethanol for ultrasonic cleaning for 15 minutes and then drying it; a thin film substrate with through holes is obtained;

[0067] 2) Accurately weigh 10g Bi 0.5 Sb 1.5 Te3 powder, 0.612 g of bisphenol F diglycidyl ether epoxy resin, 0.521 g of methyl hexahydrophthalic anhydride, 0.123 g of 2-ethyl-4-methylimidazole, and 1.8 g of butyl glycidyl ether were mechanically stirred and then ultrasonically dispersed to obtain a thermoelectric slurry;

[0068] The obtained thermoelectric paste was printed on a thin film substrate with through holes using a screen printer and dried in vacuum at 100 °C for 3 h to obtain Bi 0.5 Sb 1.5 Te3 thermoelectric thin film;

[0069] 3) placing a piece of carbon paper of the same size on the upper and lower sides of the thermoelectric film obtained in step 2), and then wrapping the carbon paper around the side of the thermoelectric film to obtain a thermoelectric film wrapped with carbon paper;

[0070] 4) The obtained Bi 0.5 Sb 1.5 The Te3 thermoelectric film was placed in a spark plasma sintering furnace, and the initial sintering pressure was set to 7MPa, the sintering temperature was 300℃, the sintering pressure was 15MPa (the heating and pressure time was about 10min), the heating rate was 27℃ / min, and the temperature and pressure were kept for 10min to obtain a Bi film with a final thickness of about 150μm. 0.5 Sb 1.5 Te3 thermoelectric thin film.

[0071] Example 5

[0072] A method for preparing a flexible bismuth telluride-based film with strong texture and high thermoelectric performance, using a film substrate with through holes, comprises the following steps:

[0073] 1) using laser etching technology to make circular through holes with a diameter of 300 μm and a spacing of 1500 μm on a polyimide substrate with a diameter of 25 mm and a thickness of 125 μm in an array distribution manner, and then ultrasonically cleaning it in anhydrous ethanol for 15 minutes and then drying it; obtaining a thin film substrate with through holes;

[0074] 2) Accurately weigh 10g Bi 0.5 Sb 1.5 Te3 powder, 0.612 g of bisphenol F diglycidyl ether epoxy resin, 0.521 g of methyl hexahydrophthalic anhydride, 0.123 g of 2-ethyl-4-methylimidazole, and 1.8 g of butyl glycidyl ether were mechanically stirred and then ultrasonically dispersed to obtain a thermoelectric slurry;

[0075] The obtained thermoelectric paste was printed on a thin film substrate with through holes using a screen printer and dried in vacuum at 100 °C for 3 h to obtain Bi 0.5 Sb 1.5 Te3 thermoelectric thin film;

[0076] 3) placing a piece of carbon paper of the same size on the upper and lower sides of the thermoelectric film obtained in step 2), and then wrapping the carbon paper around the side of the thermoelectric film to obtain a thermoelectric film wrapped with carbon paper;

[0077] 4) The obtained Bi 0.5 Sb 1.5 The Te3 thermoelectric film was placed in a spark plasma sintering furnace, and the initial sintering pressure was set to 7MPa, the sintering temperature was 300℃, the sintering pressure was 30MPa (the heating and pressure increase time was about 45min), and the heating rate was 6℃ / min. The final Bi film with a thickness of about 150μm was obtained. 0.5 Sb 1.5 Te3 thermoelectric thin film.

[0078] Comparative Example 1

[0079] A method for preparing a flexible bismuth telluride-based film using an SPS process, wherein the preparation method is substantially the same as that of Example 1, except that carbon paper is not wrapped in step 2).

[0080] The results show that the surface of the film obtained after sintering is uneven and has no metallic luster, while the internal structure is loose, making it impossible for the entire film to form a film and it is very easy to fall off the substrate.

[0081] Comparative Example 2

[0082] A method for preparing a flexible bismuth telluride-based film using an SPS process, wherein the preparation method is substantially the same as that of Example 1, except that the heating rate used in step 3) is 16° C. / min.

[0083] The results show that the surface of the sample obtained by rapid temperature sintering has a metallic luster, but there are many cracks on the surface of the film, and the substrate of the film is not only black but also very brittle and easy to crack, making it impossible to form a complete film.

[0084] The Bi prepared in Examples 1 to 5 0.5 Sb 1.5 Te3 thermoelectric film was subjected to X-ray diffraction analysis, scanning electron microscopy characterization and thermoelectric performance testing, and the results are as follows:

[0085] Figure 1 Bi obtained in Example 0.5 Sb 1.5 The relationship curves between the conductivity (a), Seebeck coefficient (b), power factor (c) and test temperature of the Te3 thermoelectric film at different positions (edge ​​and middle part); it can be seen that the film without through holes prepared in Example 1 has the problem of uneven electrical transport performance, and the data measured by sampling in different areas are quite different.

[0086] Figure 2 Bi prepared in Example 2 0.5 Sb 1.5 The relationship between the conductivity (a), Seebeck coefficient (b), power factor (c) and the test temperature at different positions (edge ​​and middle part) of the Te3 thermoelectric film; it can be seen that the electrical transport performance of the film with through holes prepared in Example 2 is uniform, compared with Figure 1 It can be seen that the through holes prepared in Example 2 not only solve the problem of uneven current and temperature distribution in the film, but also improve the electrical transport performance of the film as a whole.

[0087] Figure 3 Bi prepared in Examples 1 to 5 0.5 Sb 1.5 The X-ray diffraction patterns of Te3 thermoelectric films show that the characteristic diffraction peaks of the films prepared in Examples 1 to 5 can be compared with those of the rhombohedral Bi 0.5 Sb 1.5 The diffraction peaks of Te3 standard card (JCPDS 49-1713) correspond one to one, and no diffraction peaks of the second phase appear, indicating that the films prepared by spark plasma sintering technology are all single-phase Bi 0.5 Sb 1.5 Te3.

[0088] The orientation factors F of the (000l) plane of the film calculated by the Lotgering method are 40%, 69%, 43%, 38% and 78% respectively, indicating that the bismuth telluride film with high (000l) preferred orientation can be prepared by spark plasma sintering technology. By comparing the orientation factors of Examples 1 and 2, it is found that a higher orientation degree can be obtained by using a substrate with through holes; by comparing the orientation factors of Examples 2 and 3, it is found that the higher the sintering temperature, the higher the (000l) preferred orientation degree of the obtained film; by comparing Examples 2 and 4, it is found that the slower the heating rate, the higher the (000l) preferred orientation degree of the obtained film; by comparing the orientation factors of Examples 2 and 5, it is found that the greater the sintering pressure, the higher the (000l) preferred orientation degree of the obtained film.

[0089] Figure 4 a is Bi prepared in Example 2 0.5 Sb 1.5 Backscattered electron image (BEI) of a cross section of a Te3 thermoelectric thin film, with an average thickness of about 150 μm; Figure 4 b~f are respectively Bi prepared in Examples 1~5 0.5 Sb 1.5 From the secondary electron image (SEI) of the cross section of the Te3 thermoelectric film, it can be seen that the grains of the thermoelectric films prepared in Examples 1 to 5 are closely arranged and have obvious textures; at the same time, the thermoelectric film (Example 1) obtained by printing on a substrate without through holes is not as dense as the thermoelectric film obtained by printing on a substrate with through holes; and the higher the sintering temperature and the greater the sintering pressure of the plasma sintering process, the higher the density and (000l) preferred orientation of the obtained film. In addition, the density of the film prepared in Example 5 calculated by the Archimedean drainage method can reach 6.85g / cm 3 , which is much higher than the 4.62 g / cm prepared by hot pressing curing method reported in recent years. 3 , and can also match the density of bulk bismuth telluride thermoelectric materials prepared by SPS (5-7 g / cm 3 about).

[0090] Depend on Figure 5 From a to c, it can be seen that the thermoelectric films prepared in Examples 1 to 5 all have good electrical transport performance, especially the power factor of the thermoelectric film prepared in Example 5 reaches 2.62 mW·K -2 ·m -1 , very close to Bi 0.5 Sb 1.5 The power factor of Te3 polycrystalline bulk material (2.7mW·K -2 ·m -1 ).from Figure 5It can be seen from the figure that the single-arm devices assembled using the thin films prepared in Example 1 and Example 5 both have cooling capabilities. In particular, the cold-end cooling temperature difference of the single-arm device assembled using the thin film prepared in Example 5 reaches 1.3K, which is much higher than the currently reported optimal value of 0.7K.

[0091] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A method for preparing a flexible thermoelectric film with strong texture and high thermoelectric performance, characterized in that: The steps include: 1) preparing a thermoelectric slurry, transferring the slurry onto an insulating film substrate by a printing method, and preparing a thermoelectric film after drying; 2) placing carbon paper on the surface and side of the obtained thermoelectric film to carbon-coat the thermoelectric film sample; 3) Perform spark plasma sintering to obtain flexible thermoelectric films with strong texture and high electrothermal conversion performance; The spark plasma sintering system in step 3) includes: initial pressure of 2~15MPa, sintering temperature of 200~400℃, sintering pressure of 15~50MPa, heat preservation and pressure holding sintering time of 5~30min; wherein the heating rate adopted is 5~15℃ / min.

2. The method according to claim 1, characterized in that: A through hole perpendicular to the surface of the substrate is arranged on the thin film substrate.

3. The method according to claim 2, characterized in that The through hole in step 1) is arranged in a direction perpendicular to the surface of the film substrate; the cross-sectional area of ​​the through hole is 0.05~0.3mm 2 , the through hole spacing is 0.1~2.5mm.

4. The method according to claim 1, characterized in that: The insulating film substrate is made of any one of polyimide, polyethylene terephthalate, polyethylene naphthalate and glass cloth.

5. The method according to claim 1, characterized in that The thermoelectric slurry in step 2) is obtained by adding thermoelectric powder into a binder solution and mixing them evenly.

6. The method according to claim 5, characterized in that The thermoelectric powder in the thermoelectric slurry is p Type or n Type Bi2Te3 or Sb2Te3; the content of thermoelectric powder is 40~80wt%.

7. The method according to claim 5, characterized in that The binder in the binder solution in step 2) is at least one of epoxy resin, polyvinylidene fluoride resin, acrylic resin, polyurethane resin and cellulose resin.

8. The method according to claim 1, characterized in that The printing method in step 2) is selected from any one of screen printing, spin coating, brushing, dispensing printing, inkjet printing, and gravure printing.

9. A flexible thermoelectric film prepared by the method according to any one of claims 1 to 8.